Student review of doctor-patient communication skills training in a South African undergraduate medical programme - D Swinfen; M Labuschagne; G Joubert (South African Medical Association, 2022)
Background. Barriers to the training of doctor-patient communication in the South African (SA) context have been well explored through qualitative research at several SA medical schools. However, this aspect of training has not been reviewed in a systematic way by a large number of students. A student review of doctor-patient communication skills training in the undergraduate medical programme of a medical school in SA was obtained to improve training and identify further research needs. Objective. To investigate doctor-patient communication skills training in the undergraduate programme of a medical school in SA to identify shortcomings and further research needs. Methods. A descriptive, cross-sectional design was used. Data were collected through an anonymous questionnaire based on Harden's extended vision of the curriculum. Printed anonymous questionnaires, distributed to all the fourth- and fifth-year undergraduate medical students, were analysed quantitatively. Open-ended questions were analysed qualitatively using grounded theory. Results. The sample comprised 106/132 fifth-year students (response rate 80.3%) and 65/120 fourth-year students (response rate 54.2%). Frequent training in history-taking was reported by >75% of students, while >60% reported infrequent training in breaking bad news. More than 50% of participants indicated that senior doctors seldom or never modelled patient-centred communication in the clinical teaching milieu. Students preferred experiential learning to didactic methods. Conclusion. Medical students want to see patient-centred communication unequivocally modelled in the clinical setting. A greater emphasis on practical training in context-specific communication skills is required. Positive role-modelling is needed in the clinical environment.